Inheritance in the Perspective of Customary Law and the Compilation of Islamic Law - Dimyati, Yayat (STAI Miftahul Ula Nganjuk, 2025)
Inheritance is an important part of social life that regulates the transfer of inheritance from the testator to the heirs. In Indonesia, the inheritance system is regulated in two main legal frameworks, namely customary inheritance law and Islamic inheritance law contained in the Compilation of Islamic Law (KHI). This article discusses the differences and similarities between the two legal systems, including the basic principles, principles, and mechanisms of inheritance distribution applied in society. Customary inheritance law tends to vary because it is influenced by local culture and the prevailing kinship system, such as patrilineal, matrilineal and bilateral. Meanwhile, Islamic inheritance law is sourced from the Qur'an and Hadith with more structured and binding principles of division. This article also highlights the role of KHI in providing legal certainty for Muslims in Indonesia as well as the challenges in harmonising customary and Islamic inheritance laws in daily practice.